Stimuli-responsive drug delivery systems based on mesoporous silica nanoparticles - Wong, Eddy Mun Fei (2018)
With the development in Nanotechnology, Nano-sized drug carrier using Mesoporous Silica Nanoparticles (MSNPs) as a platform has been heavily investigated and it has demonstrated its effectiveness as a potential drug carrier system for anticancer drugs, such as Doxorubicin. This is attributed to the flexibility in modifying the properties of MSNPs to the desired design and parameters in mind. Besides that, surface functionalisation of MSNPs with stimuli responsive trigger has shown remarkable enhancement to the system as this added feature allows the release of drug selectively under specific environment and condition. In this dissertation, effectiveness of intracellular stimuli responsive ligands, such as disulfide bond and acetal linkage with less than 5 synthetic steps, will be investigated. The systems will be tested in vitro to determine the sensitivity of the ligand under specific conditions, followed by cellular and confocal studies using HeLa cells to demonstrate the toxicity and effectiveness as a drug delivery system. With this goal in mind, redox-responsive will be presented in chapter 2, along with dual responsive pH and redox responsive ligand in chapter 3. After which, doxorubicin hydrochloride (DOX) will be loaded into MSNPs as a chemotherapeutic drug before functionalisation of respective ligands onto MSNPs surface. Next, a series of characterization work was carried out to investigate the properties and demonstrate the efficacy of the system. In conclusion, the systems above have demonstrated the effectiveness of intracellular stimuli responsive ligand through the selective release of drug under redox or acidic environment whilst minimising premature release leakage under physiological condition. With this result, it can be concluded that the above systems are capable to serve as drug delivery carrier by minimising side effects from DOX and enhance toxicity to the cancerous cells.